1990
DOI: 10.1056/nejm199011153232001
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Glucose Metabolism in Adults with Hyperactivity of Childhood Onset

Abstract: Glucose metabolism, both global and regional, was reduced in adults who had been hyperactive since childhood. The largest reductions were in the premotor cortex and the superior prefrontal cortex--areas earlier shown to be involved in the control of attention and motor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
311
2
22

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 848 publications
(361 citation statements)
references
References 22 publications
22
311
2
22
Order By: Relevance
“…Studies on the SHR implicate dopaminergic and noradrenergic systems de Villiers et al 1995;Papa et al 1998;King et al 2000) but do not support a simple theory of altered dopamine neurotransmission in ADHD. Structural brain imaging studies have shown abnormalities in the frontal lobe and subcortical structures (globus pallidus, caudate, corpus callosum), regions known to be rich in dopamine neurotransmission and important in the control of attention and response to organization (Lou et al 1990;Zametkin et al 1990;Rubia et al 1997). The most consistent findings from functional neuroimaging studies in humans are hypoactivity of frontal cortex and subcortical structures, usually on the right side (Faraone and Biederman, in press).…”
Section: Evidence Supporting a Dopamine Hypothesis In Adhd And The Comentioning
confidence: 99%
“…Studies on the SHR implicate dopaminergic and noradrenergic systems de Villiers et al 1995;Papa et al 1998;King et al 2000) but do not support a simple theory of altered dopamine neurotransmission in ADHD. Structural brain imaging studies have shown abnormalities in the frontal lobe and subcortical structures (globus pallidus, caudate, corpus callosum), regions known to be rich in dopamine neurotransmission and important in the control of attention and response to organization (Lou et al 1990;Zametkin et al 1990;Rubia et al 1997). The most consistent findings from functional neuroimaging studies in humans are hypoactivity of frontal cortex and subcortical structures, usually on the right side (Faraone and Biederman, in press).…”
Section: Evidence Supporting a Dopamine Hypothesis In Adhd And The Comentioning
confidence: 99%
“…The frontal cortex is also implicated as a substrate for ADHD and MPH with accumulating evidence pointing to abnormalities in structural volume (Castellanos et al, 1996) and function (Bush et al, 1999;Rubia et al, 1999;Schweitzer et al, 2000;Vaidya et al, 1998;Zametkin et al, 1990) in this region in subjects with ADHD. Early PET-imaging studies on stimulant administration (acute oral, chronic oral, and intravenous administration) showed a lack of effect on frontal glucose metabolism in adults with ADHD (Ernst et al, 1994(Ernst et al, , 1997Matochik et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In each instance, however, the direction of these changes (vs. regional control values) is different than that which we observed in TS patients. Obsessive compulsive disorder appears to be associated with in creased metabolic rates in the orbitofrontal cortices and basal ganglia (Baxter et al 1987;Nordahl et al 1989;Swedo et al 1989), and ADHD is associated with decreases in superior sensorimotor structures, centered in the premotor cortices (Zametkin et al 1990) .…”
Section: Relationship To Other Functional Neuroimaging Studiesmentioning
confidence: 99%